Peranan apoteker dalam pelayanan pemberian swamedikasi terhadap pasien peserta bpjs kesehatan - Ilyas, Zakiya Zahro (Maliki Interdisciplinary Journal, 2025)
Self-medication is a practice where patients can use over-the-counter drugs and health products to treat mild or non-serious symptoms or medical conditions. In the context of the Health Social Security Organizing Agency (BPJS), the role of pharmacists in providing self-medication is very important. In this study, pharmacists are health workers who are trained to provide information and recommendations on the appropriate and safe use of drugs. The method used in this research is a study of relevant literature. The data used to analyze the role of pharmacists in providing self-medication to patients participating in BPJS health. The aspects studied include the pharmacist's ability to provide information on how to use drugs, supervise side effects, and improve the patient's quality of life. The results showed that the role of pharmacists is very important in providing self-medication to patients participating in the Health BPJS. The presence of pharmacists in the scope of health workers can help patients understand the use of drugs and ensure the safe and effective use of drugs. Further research and collaborative efforts between pharmacists and health institutions are needed to continue to improve the quality of self-medication provided to patients.